2022
DOI: 10.5937/ejae19-39110
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture in SMEs: An investigation of managers' vs employees' perceptions

Abstract: Purpose. This paper aims to assess the organizational culture exposed by small and medium-sized companies (SMEs). In other words, we examine the relationship between leadership styles, organizational culture and organizational performance. In order to investigate the role of organizational culture, it is fundamental to analyze the leadership styles in relation to the types of culture, to identify how these are related and well aligned so that they can help the SMEs to be more effective, favoring their innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…This suggests that organizational culture is not only a reflection of the institution's values and norms but also a key determinant of its ability to navigate and adapt to challenging circumstances, ultimately shaping its capacity for long-term sustainability and success. Mileva and Hristova (2022) suggest that organizations should use established models developed by reputable authors or internal methodologies to evaluate their organizational cultures. Additionally, they emphasize the importance of maintaining alignment and consistently pursuing improvement in order to enhance organizational efficiency and ensure long-term sustainability.…”
Section: Importance Of Organizational Culturementioning
confidence: 99%
“…This suggests that organizational culture is not only a reflection of the institution's values and norms but also a key determinant of its ability to navigate and adapt to challenging circumstances, ultimately shaping its capacity for long-term sustainability and success. Mileva and Hristova (2022) suggest that organizations should use established models developed by reputable authors or internal methodologies to evaluate their organizational cultures. Additionally, they emphasize the importance of maintaining alignment and consistently pursuing improvement in order to enhance organizational efficiency and ensure long-term sustainability.…”
Section: Importance Of Organizational Culturementioning
confidence: 99%
“…Since it spreads almost throughout the organization, fraud eventually became a culture in the organization, performed in the congregation from the leaders to the subordinates (Cohen, Ding, Lasaga & Stolowy, 2010). Hristova and Mileva (2022) found that organizational culture in small and medium-sized entities plays an important role in employee perceptions. Some authors pointed out pandemic effects on work organization and employee behaviour (Stanković & Radojević, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%